(untitled) (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2022)
This paper will attempt to explore the multiple connections of influences between various avant-garde composers in their approach to the tango universe. From the early composition of Erik Satie’s Le Tango perpetuel -at the height of the rioplatense genre in Paris at the beginning of the century- through John Cage’s Perpetual tango, to the tangos of Argentine composers Mariano Etkin and Gerardo Gandini at the beginning of the 21st century. While the reception of both Satie and Cage adapted stylistic features of tango to their own aesthetic quests, in the case of Gandini and Etkin we would like to show how their tangos are not only inscribed in their own theoretical and stylistic interests in dialogue with the tradition of the genre, but also provide new perspectives of future development.